Story Dan Status Pada Sosial Media Mahasiswa Universitas Islam Negeri Antasari (Studi Tentang Pengaruh Motivasi Intrinsik Dan Ekstrinsik Terhadap Partisipasi E-Wom Mahasiswa) - Rezani, Muhammad Rizki; Juhaidi, Ahmad; Pratiwi, Anggia Hefi; julianti, Julianti (Jurnal Ilmiah Wahana Pendidikan, 2023)
E-Wom Has A Very Significant Influence On The Decisions Of Prospective Students In Choosing The Universities They Are Interested In. This Study Aims To Identify And Analyze Intrinsic And Extrinsic Motivation And E-Wom Participation Of Antasari State Islamic University Students, Which Include Efforts To Create Statuses, Share Reviews, Comments, And Recommendations Through Social Media. Data Collection Through Questionnaires Distributed To Students Online. There Were 213 Participants In This Study Consisting Of 131 Women And 82 Men. The Results Of The Linear Regression Test Show That There Is A Significant Influence Of Intrinsic And Extrinsic Motivation On Student E-Wom Participation. The Results Of This Study Indicate That Intrinsic And Extrinsic Motivation Have An Important Role In Encouraging Students To Be Active In Providing Reviews And Comments On Social Media Related To Their Schools/Madrasas And Colleges. Based On These Findings, Universities And Educational Institutions Can Develop Programs And Initiatives Aimed At Facilitating Student Participation In E-Wom. By Leveraging The Power Of E-Wom As A Marketing Strategy, Educational Institutions Can Influence The Decisions Of Prospective Students In Choosing Educational Institutions Or Colleges That Suit Their Interests.